2003
DOI: 10.1021/ie030561+
|View full text |Cite
|
Sign up to set email alerts
|

Extractive Desulfurization and Denitrogenation of Fuels Using Ionic Liquids

Abstract: Two types of ionic liquids, 1-alkyl-3-methylimidazolium [AMIM] tetrafluoroborate and hexafluorophosphate and trimethylamine hydrochloride (AlCl 3 -TMAC), were demonstrated to be potentially applicable for sulfur removal from transportation fuels. EMIMBF 4 (E ) ethyl), BMIMPF 6 (B ) butyl), BMIMBF 4 , and heavier AMIMPF 6 showed high selectivity, particularly toward aromatic sulfur and nitrogen compounds, for extractive desulfurization and denitrogenation. The used ionic liquids were readily regenerated either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
339
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(353 citation statements)
references
References 19 publications
(30 reference statements)
11
339
0
3
Order By: Relevance
“…As described throughout this book, ILs present exceptional properties such as high solvent abilities, negligible vapor pressures, extremely high electrical conductivities, chemical and thermal stability [34][35] that have been exploited in applications as diverse as in organic synthesis [36][37], catalysis [38][39], biocatalysis [40][41], separations [42], extraction [43], dissolution [44], polymerization reactions [45] and electrochemistry [46]. In petroleum industry, ILs have found wide applications as corrosion inhibitors [14,47], as inhibitors of asphaltene precipitation [48] and for removing pollutants from refineries feedstocks [13].…”
Section: Ionic Liquids As Surfactantsmentioning
confidence: 99%
“…As described throughout this book, ILs present exceptional properties such as high solvent abilities, negligible vapor pressures, extremely high electrical conductivities, chemical and thermal stability [34][35] that have been exploited in applications as diverse as in organic synthesis [36][37], catalysis [38][39], biocatalysis [40][41], separations [42], extraction [43], dissolution [44], polymerization reactions [45] and electrochemistry [46]. In petroleum industry, ILs have found wide applications as corrosion inhibitors [14,47], as inhibitors of asphaltene precipitation [48] and for removing pollutants from refineries feedstocks [13].…”
Section: Ionic Liquids As Surfactantsmentioning
confidence: 99%
“…The application of mild process conditions (ambient pressure and temperature) and the fact that no hydrogen is needed are additional advantages compared to HDS. 4 ], and heavier trimethylamine hydrochloride (AlCl 3 -TMAC) showed high selectivity, particularly toward aromatic sulfur and nitrogen compounds, for extractive desulfurization and denitrogenation (58). The used ILs were readily regenerated either by distillation or by water displacement of absorbed molecules.…”
Section: Koelmentioning
confidence: 99%
“…13 Zhang et al also stated that the sulfur compounds with a higher density of aromatic π-electron are favorably absorbed by ionic liquids. 42,43 The relatively large differences in the partition coefficients of the individual sulfur compounds may be due to the difference of aromatic π-electron density of sulfur compounds. These results suggested that the extractive performance becomes better with the increase of the aromatic π-electron density.…”
Section: Introductionmentioning
confidence: 99%